Using topic modeling to find main discussion topics in brazilian political websites - Bertalan, Vithor G.; Ruiz, Evandro Eduardo S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Knowing the main discussion topics debated by the general public is a valuable asset to politicians and professionals involved with politics. Lately, alternative media websites became popular venues in which political ideas are debated without the influence of mainstream media. In this article, we propose the construction of a topic modeling framework, using LSI, LDA, and HDP, to identify main discussion issues in political websites. Experiments show that these models presented results similar to state of the art, offering a viable solution to track political discourse in left-wing and right-wing websites.